PERLINDUNGAN HUKUM TERHADAP PEKERJA DALAM PERJANJIAN KERJA WAKTU TERTENTU DI PT. DASA WINDU AGUNG BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (STUDI KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 859 K/PDT.SUS-PHI/2019) - sandra carmelita; Ahmad Redi (Fakultas Hukum Universitas Tarumanagara, 2021)
Legal protection for workers in a certain time work agreement at PT. Dasa Windu Agung has an important role to guarantee the main rights possessed by workers without discrimination to achieve the welfare of workers and their families. This research aims to find out whether the judges' considerations in the decision number 859K / Pdt.Sus-PHI / 2019 are in accordance with Act of The Republic Of Indonesia Number 13 year 2003 concerning Manpower and to find out the legal protection of workers in a certain time work agreement at PT.Dasa Windu Agung Based on Act of The Republic Of Indonesia Number 13 year 2003 concerning Manpower. The type of research used in this research is normative legal research and uses primary legal materials including laws, secondary legal materials in the form of books, using a statutory approach and a case approach related to the problems under study. The author analyzes the data with a deductive method. The judge's consideration in the decision number 859K / Pdt.Sus-PHI / 2019 was a little wrong because the nature of the job for the object of the job was permanent worker, this was because the job was the main job at PT. Dasa Windu Agung as production. Therefore, unituk get rights as workers are given legal protection in the form of wage protection, social security protection for workers and security protection for work.